Primary care and chronic disease: the intersection of comfort and specialty involvement – a cross‐sectional study. Issue 3 (15th August 2016) - Schreiner, Andrew; Simpson, Kit
Abstract: Background: Primary care referrals to specialty physicians play an integral role in patient care and health care costs. Multiple factors play into the primary care physician's decision to refer, including comfort managing particular conditions. As the burden of chronic disease climbs, the relationship between patients, primary care physicians and specialists in accurately diagnosing, managing and treating chronic conditions needs clarity. The objective of this study is to assess the relationship between specialty physician involvement and the care of three chronic conditions: diabetes mellitus (DM), chronic kidney disease (CKD) and systemic lupus erythematosus (SLE). Methods: To achieve this objective, we performed a cross‐sectional study of 2013 MarketScan data (875 million billing records) for three chronic medical conditions. Participants were identified in the dataset by having received a diagnosis code for DM, CKD or SLE in an outpatient care setting during 2013. The study compared proportions of outpatient visits with specialty physicians in endocrinology, nephrology and rheumatology for patients with DM, CKD and SLE respectively. Results: Data included 1 615 609 visits with the diagnosis of DM, 158 424 visits with the diagnosis of CKD and 103 910 visits with SLE. Diabetic patients met endocrinologists (10.2%) at a smaller proportion of their visits than patients with CKD saw nephrologists (41.2%, P < 0.0001). Further, CKD patients met with nephrologists (41.2%) at a significantly fewer proportion of outpatient visits than SLE patients saw rheumatologists (51.8%, P < 0.0001). Conclusions: Differences in primary care physicians' comfort with diagnosis, therapy and adherence to published guidelines affect the rate with which primary care providers seek specialty consultation.